Development of a Palliative Telehealth Pilot to Meet the Needs of the Nursing Home Population. Issue 5 (October 2021) - Baxter, Kelly E.; Kochar, Sandeep; Williams, Cheryl; Blackman, Carolyn; Himmelvo, Jane
Abstract : Many older adults will spend their final days in a skilled nursing facility because of multiple complex conditions. Patients with unclear goals of care are at higher risk of rehospitalization and burdensome care at end of life. Palliative care has been shown to improve outcomes for this patient population; however, access is limited because of the small number of boarded specialists nationwide. Telehealth offers the ability to expand the reach of palliative care to both underserved geographies and community settings. This quality improvement pilot project details the development and implementation of a telehealth palliative care program available to nursing home residents. Eight nursing homes, in the New England region of the United States, participated in the 4-month pilot. The palliative telehealth program offered real-time access to a palliative care specialist able to provide symptom management, goals-of-care discussions, and Medical Orders for Life-Sustaining Treatment completion. The pilot shows promising outcomes including code status change, Medical Order for Life-Sustaining Treatment form completion, and reduced hospitalizations supporting the benefit of comprehensive goals-of-care discussions for frail older adults living in a nursing home. As health care moves into the digital age, telemedicine plays a large role in the delivery of essential patient care. Provision of palliative specialists by telehealth allows the opportunity to address the unmet needs of this frail population.